Assessing the sociology of sport: On media and representations of sportswomen. (June 2015) - Bruce, Toni
On the 50th anniversary of the ISSA and IRSS, Toni Bruce – one of the leading scholars in understanding how media fashion gendered understandings of sport – considers the development of sociology of sport research on media with particular focus on representations of sportswomen. The trajectory of research strategies to study media representations of sportswomen has evolved, to become interdisciplinary, intersectional and theoretically sophisticated. A key challenge for sociology of sport research, both generally and with regards to media specifically, has been to gain traction and exposure beyond the boundaries of the field. While media-centred studies have risen on the research agenda, new challenges remain in engaging understandings of increasingly interactive media in the experience of sport. The future of research on media and sportswomen will face ongoing challenges, given the consistency of mainstream media marginalization of women's sport; such findings portend the need to broaden the sociological frame to include a 'psychodynamic dimension' to understand better how emerging theoretical interest in affect or emotion may help explain how well worn representational grooves about women and sport have remained surprisingly entrenched in culture.